2020
DOI: 10.1038/s41598-020-74819-x
|View full text |Cite
|
Sign up to set email alerts
|

Syringa vulgaris leaves powder a novel low-cost adsorbent for methylene blue removal: isotherms, kinetics, thermodynamic and optimization by Taguchi method

Abstract: In this study, the potential of a new low-cost adsorbent, Syringa vulgaris leaves powder, for methylene blue adsorption from aqueous solution was investigated. The adsorbent surface was examined using SEM and FTIR techniques. The experiments were conducted, in batch system, to find out the effect of pH, contact time, adsorbent dose, initial dye concentration, temperature and ionic strength on dye adsorption. The process is best described by Langmuir isotherm and the pseudo second order kinetic model. Maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 56 publications
10
43
0
Order By: Relevance
“…Therefore, the peak occurring within range 1596–1608 cm −1 could be attributed to C=C stretching vibrations from the structure of both flavonols and iridoids [ 24 , 26 , 27 , 28 ]. Similarly, in the FT-IR spectra of S. vulgaris analyzed extracts, flavonols possess C–O–C, C=C and CH 3 functional groups which display peaks between 924–930 cm −1 , 1159–1162 cm −1 and 1385–1404 cm −1 respectively [ 20 , 23 , 27 , 28 , 29 ] ( Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, the peak occurring within range 1596–1608 cm −1 could be attributed to C=C stretching vibrations from the structure of both flavonols and iridoids [ 24 , 26 , 27 , 28 ]. Similarly, in the FT-IR spectra of S. vulgaris analyzed extracts, flavonols possess C–O–C, C=C and CH 3 functional groups which display peaks between 924–930 cm −1 , 1159–1162 cm −1 and 1385–1404 cm −1 respectively [ 20 , 23 , 27 , 28 , 29 ] ( Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 98%
“…Infrared spectroscopy is an effective and non-targeted analytical method which could non-destructively and cost-effectively detect the intrinsic quality of different plants [ 19 , 20 ]. Based on FT-IR results, it is possible to highlight a list of peaks that can be assigned to different biochemical class of compounds, which could lead to a better correlation between the chemical structure and the spectroscopic features of plants [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prices of the chemical reagents were obtained from the corresponding vendors. Some authors reported that adsorbents are usually inexpensive provided they are prepared from natural materials available in large quantities, require little processing, or are a byproduct or agricultural waste [47][48][49]. Most studies do not provide information on manufacturing costs.…”
Section: Adsorbent Materialsmentioning
confidence: 99%